Study of the mechanics of progressive collapse with simplified beam models. (15th June 2016) - Stylianidis, P.M.; Nethercot, D.A.; Izzuddin, B.A.; Elghazouli, A.Y.
Highlights: A detailed study of the beam behaviour following column removal is presented. The different collapse resisting mechanisms are assessed individually. Simplified models that describe key features of the performance are derived. Dynamic effects are incorporated through the concept of energy balance. A simplified method for prediction of the pseudo-static response characteristics is proposed. Abstract: Methods for assessing structural robustness need to move away from the traditional norms of prescriptive rules and become more similar to those used in conventional structural design. They should therefore be based on a sound understanding of the mechanics of the problem and provide quantitative indication of its effects. Several Codes and Design Guides consider the sudden column removal approach as their principal method for progressive collapse assessment. The level of robustness is defined based on the capability of the remaining structure for sustaining the additional loading imposed by the column loss. Most likely, the beams adjacent to the lost column and their supporting connections form the principal load paths. The present paper presents a detailed study of the response of those components under the conditions experienced following column removal. Suitable analysis approaches that have been previously developed at Imperial College London are employed to investigate the basic features of the behaviour, while several simplifications are applied for exploring particular effects. The study concludes with the development of a simplified method for simulating the nonlinear dynamic response of axially restrained and unrestrained beams following column removal. The capability of the new simplified method to accurately describe performance is demonstrated through a set of suitable applications presented in a separate publication.